Factores limitantes del crecimiento de organismos fotosintéticos en el embalse Sixto Durán Ballén del cantón Bolívar - Cedeño Velásquez, Gema Guadalupe (2024)
The objective of this research was to evaluate the factors affecting the growth of photosynthetic organisms in different layers of the Sixto Durán Ballén reservoir, specifically in the Epilimnion, Thermocline, and Hypolimnion. In situ (pH, temperature, dissolved oxygen, turbidity) and ex situ (BOD5, nitrates, phosphates, suspended solids) measurements were conducted on a weekly basis, from 08:00 am to 09:00 am and from 3:30 pm to 5:00 pm. The reservoir stratification was determined based on temperature measurements during monitoring, identifying the Epilimnion in the surface layer from 0 to 5 meters, the Thermocline in the intermediate layer from 6 to 11 meters, and the Hypolimnion in the deepest layer from 12 to 18 meters. Limiting factors for photosynthetic organisms in the Sixto Durán Ballén Reservoir showed the following ranges: phosphates from 9mg/l to 6mg/l, nitrates from 8mg/l to 5mg/l, and BOD5 from 16mg/l to 14mg/l. It was observed that at greater depths, the concentration of these factors decreases, indicating they are not limiting in the deeper layers. In contrast, pH (7.10 to 7.60), temperature (27°C to 31°C), dissolved oxygen (1.20mg/l to 3.5mg/l), turbidity (3 NTU to 6 NTU), and suspended solids (0.01mg/l to 0.05) were identified as limiting factors for the growth of photosynthetic organisms. These results underscore the importance of considering stratification and vertical variability of environmental parameters when analyzing their impact on aquatic ecology.